Penerapan Metode Manajemen Proyek dalam Meningkatkan Kualitas Perpustakaan Berbasis Teknologi Informasi - Heri Prasetya (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
This Best Practice writing aims to determine the application of project management methods to improve the quality of information technology-based libraries at SMP Negeri 2 Kasihan. This Best Practice writing method uses a deskriptive qualitative approach with a case study method. Data collection techniques used were participatory observation, interviews and documentation. Best Practice writing is carried out by carrying out five main stages, namely identification of activities, preparation of activity sequences, estimated time of activities, preparation of activity schedules, and controlling activity schedules. The results of the application of project management showed that the average quality value of the library before the action was 2.28 and after the action was 4.23 so that there was an increase in quality by 85%. The increase in library quality occurs because the aspects of library infrastructure have increased by 81%, before the quality value action was taken, the quality value was 2.5 and after the action was carried out by 4.0. Information technology-based library management aspects experienced an increase of 100% from the average quality before the action of 2.2 and after the action of 4.4. The increase that has a major contribution to the application of information technology is in the aspect of library automation which shows an increase of 150% because the quality before the action is 2.0 and after the action is 5.0. Meanwhile, the use of computers connected to the internet increased 100%. The use of computers connected to WiFi increased 67%. Based on these results, it can be concluded that the application of project management methods can improve the quality of technology and information-based libraries at SMP Negeri 2 Kasihan.